Antibody responses to hepatitis A virus vaccination in Thai HIV-infected children with immune recovery after antiretroviral therapy - Tavitiya Sudjaritruk (2018)
The prevalence of hepatitis A virus (HAV) protective antibody in 98 Thai HIV-infected children who achieved immune recovery after antiretroviral therapy was 12.2%. After a 2-dose HAV vaccination, 98.8% (85 of 86 children) seroconverted. The geometric mean titer was 520.95 mIU/mL. In a multivariate analysis, female gender, age <12 years and higher CD4 lymphocyte count at enrollment were predicting factors for high (≥250 mIU/mL) HAV antibody response. © 2011 Lippincott Williams & Wilkins, Inc.